A high-tortuosity holey graphene in-situ derived from cytomembrane/cytoderm boosts ultrastable potassium storage. (10th March 2023) - Xiao, Jun; Min, Xin; Lin, Yue; Yu, Qiyao; Wang, Wei; Wu, Xiaowen; Liu, Yangai; Huang, Zhaohui; Fang, Minghao
Highlights: A high-tortuosity holey graphene was successfully prepared based on the unique flake structure and chemical composition of cytomembrane and cytoderm. Benefiting from the unique nanoholes shortening the ion-diffusion length, the synergy of wrinkled and holey structure stabilizing volume fluctuation, the enhanced electronic conductivity and specific surface area. The anode achieves excellent reversible capacity, and exceptional rate capability with an ultra-long cycle lifespan in PIBs. The anode exhibits a high energy density as well as considerable cycling stability for potassium-ion full cells. Abstract: The sluggish K + kinetics and structural instability of the generally-used graphite and other carbon-based materials hinder the development of potassium-ion batteries (PIBs) for high-rate capability and long-term cycling. Herein, inspired by the unique flake structure and chemical composition of cytomembrane and cytoderm, we design high-tortuosity holey graphene as a highly efficient anode for PIBs. The flake cytomembrane and cytoderm shrink into wrinkled morphology during drying and sintering and then convert into high-tortuosity graphene after oxidative exfoliating and thermal reducing process. Meanwhile, the proteins, sugars, and glycolipids embedded in cytomembrane and cytoderm can in-situ form nanoholes with highly abundant oxygenic groups and heteroatoms around, which can be easily removed and finally the high-tortuosity holey graphene is obtained after a thermal reducing process. The stress distribution after K + intercalation confirms the optimized release of strain caused by the volume change through the finite element method. Benefiting from the unique nanoholes shortening the ion-diffusion length, the synergy of wrinkled and holey structure stabilizing volume fluctuation, and the enhanced electronic conductivity and specific surface area, the high-tortuosity holey graphene demonstrates high reversible capacities of 410 mAh g –1 at 25 mA g –1 after 150 cycles and retains 91.5% at 2 A g –1 after 2500 cycles. Graphical abstract: Image, graphical abstract